Pengaruh Pengetahuan Kewirausahaan, Praktik Kerja Industri dan Motivasi Berprestasi Terhadap Minat Berwirausaha Siswa Kelas XII Kompetensi Keahlian Pemasaran SMK Negeri Bisnis dan Manajemen Kota Padang - Meri Rahmania; Z. Mawardi Effendi (Program Magister Pendidikan Ekonomi (S2), 2014)
This research aims to analyze (1) influence of knowledge entrepreneurship, industrial work practice and motivation of entrepreneurship interest against an accomplished students of class XII marketing skills competency SMK Negeri Padang city business and management. (2) the influence of knowledge entrepreneurship entrepreneurship interest to grade XII Foreign marketing skills competency SMK Padang city business and management. (3) the influence of the working practices of the industry of interest entrepreneurship grade XII Foreign marketing skills competency SMK Padang city business and management.(4) the influence of motivation overachievers against interest entrepreneurship marketing students of SMK Negeri Padang city business and management. Type of this research is a descriptive associative. The population of this research is the entire class XII student competency expertise marketing SMK Negeri Padang city business and management, totalling 137 persons. Sample withdrawal technique with random sampling proportional to the number of samples as much as 102 people. Analysis techniques using descriptive analysis and inductive analysis: test the assumptions of classical and multiple regression analysis. Results of research: (1) knowledge entrepreneurship, industrial work practices and motivational impact of entrepreneurship interest achievers grade XII Foreign marketing skills competency SMK Padang city business and management.(2) knowledge of significant interest to the influential entrepreneurship entrepreneurship class XII student competency expertise marketing SMK Negeri Padang city business and management. (3) the working practices of influential industry significantly to interest of entrepreneurship class XII student competency expertise marketing SMK Negeri Padang city business and management.(4) an accomplished motivational effect significantly to interest students of entrepreneurship class XII student competency expertise marketing SMK Negeri Padang city business and management. Keywords: entrepreneurship, knowledge work practices, the motivation industry achievers and interest of entrepreneurship